Introduction: A handbook on territorial impact assessment (TIA) - Medeiros, E. (Territorial impact assessment, 2020)
Territorial Impact Assessment (TIA) is a relatively ‘new kid on the block’ of policy evaluation. Resting upon the holistic notion of territory, which encompasses multiple analytic dimensions (economy, society, environment, governance, spatial planning), TIA is the most complex, yet with the policy evaluation procedure with the largest potential to assess projects, programmes and policies. Indeed, policy evaluation procedures are now deeply rooted in sub-national, national and transnational territorial development strategies and processes. However, unlike the plethora of published books on Environmental Impact Assessment (EIA) and other Impact Assessment (IA) methodologies, presently no TIA handbook has been published by any major international publisher. As such, this one intends to add a substantial contribution to available literature by presenting to the interested reader the most relevant TIA methodologies that have been produced so far. Furthermore, all the chapters, written by the authors of each TIA methodology presented, provide a detailed, updated and scientifically accurate explanation of their particular purpose and methodological operation. In the end, the reader is presented with a complete set of TIA methodologies to select from based on their advantages/disadvantages for a particular case-study. For a better understanding of how all the presented TIA methodologies work, concrete examples are presented in each chapter.